POLYGAMY; REANALYZING THE MUFASSIR VIEWS OF ”ADL” - Ikhwanuddin Harahap (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Polygamy discourse is always interesting to discuss. This is due to facts on the ground which show that polygamous wives are often treated unfairly. So the concept of 'adl still needs to be explored. This research is qualitative and library research. Primary sources are tafsir books. Data collected with documentation. The data collected was analyzed by content analysis. The results of the study show that there is ’adl among tafsir experts are both in terms of al-makan (place of residence/house), al-zaman (time/turn), mata' al-makan (jewelry/ home furnishings, fair in terms of material things, namely equality, balance, equality in terms of the number of shifts to stay, livelihood which includes food, drink, clothing and housing, the husband must provide a house for each wife. Beside that, husbands may not take one wife on a trip except by lottery, husbands may not place their wives in one house except by agreement, husbands may not place their wives in one room, husband must mewathi' his wife if there are no obstacles.